Glipizide ameliorates human poly(Q) mediated neurotoxicity by upregulating insulin signalling in Drosophila disease models. - Tandon, S.; Sarkar, S. (Biochemical and Biophysical Research Communications, 2023)
Increasing reports suggest insulin signalling pathway as a putative drug target against polyglutamine [poly(Q)] disorders, such as Huntington's disease (HD), Spinocerebellar ataxias (SCA) 1, 2, 3 etc. However, studies on drug-based stimulation of insulin signalling cascade to mitigate poly(Q) pathogenesis are lacking. In our study, we adopted an evidence-based approach to examine if some established insulin stimulating drug can be utilized to restrict poly(Q) aetiology in Drosophila disease models. For the first time, we report that glipizide, an FDA approved anti-diabetic drug upregulates insulin signalling in poly(Q) expressing tissues and restricts formation of inclusion bodies and neurodegeneration. Moreover, it reinstates the chromatin architecture by improving histone acetylation, which is otherwise abrogated due to poly(Q) toxicity. In view of the functional conservation of insulin signalling pathway in Drosophila and humans, our finding strongly suggests that glipizide can be repurposed as an effective treatment strategy against the neurodegenerative poly(Q) disorders. Also, with appropriate validation studies in mammalian disease models, glipizide could be subsequently considered for the clinical trials in human patients.